Designing Time and Running Text With LED Matrix P 10 Using Arduino Uno Microcontroller - Rima Tamara Aldisa; Mohammad Aldinugroho Abdullah; Muhammad Furqon Sofyan (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
A running text is one of the media for promotion or we can call it advertising media where the writing will run and repeat. This running message or running text is very useful and helpful for someone who wants to promote a business that is running. For that date, it can be needed and a tool that is easily assembled is needed. The author made it entitled Design of Time and Running Messages with LED Matrix P 10 Using Arduino Uno. With this tool, it can be easier to promote something by displaying a running message, and this tool can also display the desired day, date, month, year